(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
To develop and validate simple, sensitive, precise, rapid and cost effective method for determination of Canagliflozin in bulk and pharmaceutical formulations as per ICH Guidelines. A simple double beam UV Spectrophotometric method has been developed and validated with different parameters such as Linearity, Precision, Repeatability, Accuracy, Robustness and Ruggedness. Canagliflozin in phosphate buffer shows maximum absorbance at 240 nm. Beer’s law was obeyed in the concentration range of 10-50 mcg ml-1.